The Impacts of Foreign Language Anxiety on Speaking Confidence: A Correlational Study in Students of the English Department of the University of Mataram - Anisa, Nisma; Udin; Saputra, Agus; Melani, Boniesta Zulandha (Program Studi Pendidikan Bahasa Inggris, 2025)
The interplay of Foreign Language Anxiety (FLA) and speaking confidence are important in the trajectory learning of the English language, and anxiety can lead to diminished students' communication ability and willingness to communicate. The current study explored the relation of FLA, with emphasis on anxiety in relation to speaking confidence, for the students of the English Department of the University of Mataram. The method used was a quantitative correlational design in which two sets of questionnaires on the concept were used to explore the variables. Descriptive statistics were used to derive the mean levels of FLA and speaking confidence, and Spearman's rank correlation was implemented to establish the strength and direction of the relationship. The analysis established three types of impacts of FLA which is cognitive, academic, and social. Overall, the correlation test found evidence of a negative relation between FLA and speaking confidence, implying that increased anxiety decreased the students' confidence to speaking English. The data highlight the need to address FLA around students learning English in the language classroom, in terms of developing students' speaking confidence and communicative competence.